Multiple Choice Question (MCQ)

The sum of the zeros of y = 3x^2 - 6x - 4 is

  1. ×

    -2

  2. ×

    -\dfrac{4}{3}

  3. ×

    \dfrac{4}{3}

  4. 2

  5. ×

    6

Collected in the board: Quadratic function

Steven Zheng posted 3 weeks ago


Answer

  1. The sum of zeros, that is, the sum of two roots of a quadratic equation ax^2=bx+c=0 is equal to -\dfrac{b}{a}

    Therefore, for quadratic function y=3x^2-6x-4

    -\dfrac{b}{a}=-\dfrac{-6}{3} =2

    The correct answer is D

Steven Zheng posted 3 weeks ago

Scroll to Top